PERANCANGAN KAMPANYE KOMUNIKASI KALENDER TANAM (KATAM) DALAM UPAYA ADAPTASI PERUBAHAN IKLIM - Azis, Abdul; Isnaini, Muhamad; Fahrimal, Yuhdi; Alhafidz, Mohammad Alhabieb (Fakultas Komunikasi & Desain Kreatif - Universitas Budi Luhur, 2017)
Background of this review is the fact that the campaign of InformationSystem of Integrated Planting Calendar/KATAM has been done on a massivescale. Notwithstanding, just many peasant know and use KATAM as aguideline.Purpose of this reviewis to determine the design of KATAMcommunication campaigns. Thisreview using secondary data,then analyzed withAISAS method. The results show, the communication through the campaign onKATAM basically already done by Balitbangtan. The campaign was carried outby using the internet and social media. KATAM campaign is quite effective.Further study need to be done to determine share of KATAM to others.